Beginning VB 2008 Databases - Vrat Agarwal, Vidya (Springer, 2017)
Beginning VB 2008 Databases teaches you everything you need to know about relational databases, SQL, and ADO.NET 2.0, giving you a sound start in developing console and Windows database applications. The book also includes chapters on the SQL Server XML data type and the LINQ enhancements to the next version of Visual Basic.